Biopolymer‐Templated Deposition of Ordered and Polymorph Titanium Dioxide Thin Films for Improved Surface‐Enhanced Raman Scattering Sensitivity. (27th October 2021) - Chen, Qing; Betker, Marie; Harder, Constantin; Brett, Calvin J.; Schwartzkopf, Matthias; Ulrich, Nils M.; Toimil‐Molares, Maria E.; Trautmann, Christina; Söderberg, L. Daniel; Weindl, Christian L.; Körstgens, Volker; Müller‐Buschbaum, Peter; et al.
Abstract: Titanium dioxide (TiO2 ) is an excellent candidate material for semiconductor metal oxide‐based substrates for surface‐enhanced Raman scattering (SERS). Biotemplated fabrication of TiO2 thin films with a 3D network is a promising route for effectively transferring the morphology and ordering of the template into the TiO2 layer. The control over the crystallinity of TiO2 remains a challenge due to the low thermal stability of biopolymers. Here is reported a novel strategy of the cellulose nanofibril (CNF)‐directed assembly of TiO2 /CNF thin films with tailored morphology and crystallinity as SERS substrates. Polymorphous TiO2 /CNF thin films with well‐defined morphology are obtained by combining atomic layer deposition and thermal annealing. A high enhancement factor of 1.79 × 10 6 in terms of semiconductor metal oxide nanomaterial (SMON)‐based SERS substrates is obtained from the annealed TiO2 /CNF thin films with a TiO2 layer thickness of 10 nm fabricated on indium tin oxide (ITO), when probed by 4‐mercaptobenzoic acid molecules. Common SERS probes down to 10 nm can be detected on these TiO2 /CNF substrates, indicating superior sensitivity of TiO2 /CNF thin films among SMON SERS substrates. This improvement in SERS sensitivity is realized through a cooperative modulation of the template morphology of the CNF network and the crystalline state of TiO2 . Abstract : The morphology and crystallinity of biotemplated titanium dioxide/cellulose nanofibril (TiO2 /CNF) thin films are studied by X‐ray scattering techniques. The TiO2 layer achieves a desired crystalline state while preserving the morphology of the CNF template. The resulting highly ordered and polymorphous TiO2 /CNF thin films display an excellent surface‐enhanced Raman scattering (SERS) performance compared to semiconductor metal oxide nanomaterial‐based SERS substrates.